PENGARUH METODE PEER TUTORING TERHADAP HASIL BELAJAR PADA PEMBELAJARAN TEMATIK KELAS II DI SEKOLAH DASAR INKLUSI - Wa’aufa, Khusana; Supratno, Haris; Rochmania, Desty Dwi (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2020)
The problem that is the focus of this research is the learning conditions of children with special needs so as not to be left behind from normal children in inclusive schools. The research objective in this study is to provide an overview of the results of the pretest and posttest when the Peer Tutoring method is used in the experimental group, to be able to provide an overview of the results of the pretest and posttest when conventional learning is used in the control group, and the latter can provide an overview of the effect of using the Peer method. Tutoring on student learning Results in class II thematic learning at SDN Bandar Kidul 2 Kediri of City (Inclusion School). This research is an experimental research, by comparing the experimental group and the control group so that the research design used is a nonequivalent control group design with comparative statistical analysis techniques. The data collection technique used in this study is a written test by passing the Likert validation test that has been conducted by lecturers and class teachers. The information analysis technique used is the T-test with normality test and hypothesis testing. For the pretest experimental group normality test 0.200 <0.349 and 0.071 <0.349, then the pretest control group normality test 0.200 <0.349 and posttest 0.200 <0.349 which can be concluded that the two data were normally distributed. And to test the experimental group's hypothesis obtained T count 18.828 which this score is higher than T table 2.145. Thus it can be said that Ho is rejected and Ha is accepted. From these results it can be concluded that the learning achievement before and after using the peer tutoring method is different.